Computational logistics : 7th International Conference, ICCL 2016, Lisbon, Portugal, September 7-9, 2016, Proceedings /: 7th International Conference, ICCL 2016, Lisbon, Portugal, September 7-9, 2016, Proceedings. (2016) - Unknown
No abstract available